2003
DOI: 10.1074/jbc.m208967200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Novel Regulatory 40-kDa Mammary Gland Protein (MGP-40) Secreted during Involution

Abstract: We have determined the crystal structure of a novel regulatory protein (MGP-40) from the mammary gland. This protein is implicated as a protective signaling factor that determines which cells are to survive the drastic tissue remodeling that occurs during involution. It has been indicated that certain cancers could surreptitiously utilize the proposed normal protective signaling by proteins of this family to extend their own survival and thereby allow them to invade the organ and metastasize. In view of this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 28 publications
4
79
1
Order By: Relevance
“…The crystallographic three-dimensional structure of human [10,11] and goat YKL-40 [12] are described but the site and mode of binding to cell surface receptors is not yet known. YKL-40 is a heparin and chitin-binding lectin [3,13] without chitinase activity [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…The crystallographic three-dimensional structure of human [10,11] and goat YKL-40 [12] are described but the site and mode of binding to cell surface receptors is not yet known. YKL-40 is a heparin and chitin-binding lectin [3,13] without chitinase activity [1,13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an x-ray structure for one member of the chitolectin class of proteins MGP40 (PDB ID: 1LJY) was determined [5]. The structure is consistent with the (β/α) 8 barrel topology of the Family 18 glycosidase proteins .…”
Section: Mgp40mentioning
confidence: 61%
“…1). We found that since Arg84 is conserved between the two proteins, it is not the cause for the lack of oligosaccharide binding in MGP40 as proposed by Mohanty et al [5]. Hence we compared the aromatic residues in both proteins, focusing on the Trp and Tyr residues present in the floor of the binding groove that are likely to interact strongly with the sugar molecules.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations